Phylogenomics of alligator lizards elucidate diversification patterns across the Mexican Transition Zone and support the recognition of a new genus. (25th November 2021) - Blair, Christopher; Bryson, Robert W; García-Vázquez, Uri O; Nieto-Montes De Oca, Adrián; Lazcano, David; Mccormack, John E; Klicka, John
Abstract: Genomic data continue to advance our understanding of species limits and biogeographic patterns. However, there is still no consensus regarding appropriate methods of phylogenomic analysis that make the best use of these heterogeneous data sets. In this study, we used thousands of ultraconserved element (UCE) loci from alligator lizards in the genus Gerrhonotus to compare and contrast species trees inferred using multiple contemporary methods and provide a time frame for biological diversification across the Mexican Transition Zone (MTZ). Concatenated maximum likelihood (ML) and Bayesian analyses provided highly congruent results, with differences limited to poorly supported nodes. Similar topologies were inferred from coalescent analyses in Bayesian Phylogenetics and Phylogeography and SVDquartets, albeit with lower support for some nodes. All divergence times fell within the Miocene, linking speciation to local Neogene vicariance and/or global cooling trends following the mid-Miocene Climatic Optimum. We detected a high level of genomic divergence for a morphologically distinct species restricted to the arid mountains of north-eastern Mexico, and erected a new genus to better reflect evolutionary history. In summary, our results further advocate leveraging the strengths and weaknesses of concatenation and coalescent methods, provide evidence for old divergences for alligator lizards, and indicate that the MTZ continues to harbour substantial unrecognized diversity.